Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Multiplication

Consider this system:

3x + (1/2)y = 3
6x - y = 2

Which of the following operations would eliminate the x-terms if the two equations were added together afterward?

A. Multiply the first equation by -6
B. Multiply the first equation by -2
C. Multiply the first equation by 2
D. Multiply the first equation by 6

Which of the following operations would eliminate the y-terms if the two equations were added together afterward?

A. Multiply the first equation by -2
B. Multiply the first equation by 2
C. Multiply the second equation by -2
D. Multiply the second equation by 2

Use elimination to solve the system. The solution is ___ .


Sagot :

We are given the system of equations:

[tex]\[ 3x + \frac{1}{2}y = 3 \][/tex]

[tex]\[ 6x - y = 2 \][/tex]

### Part 1: Eliminating the [tex]\(x\)[/tex]-terms

To eliminate the [tex]\(x\)[/tex]-terms, we need to manipulate the equations so that the coefficients of [tex]\(x\)[/tex] in both equations are equal in magnitude but opposite in sign.

1. Original equations:
[tex]\[ 3x + \frac{1}{2}y = 3 \quad \text{(1)} \][/tex]
[tex]\[ 6x - y = 2 \quad \text{(2)} \][/tex]

2. Multiply the first equation (1) by [tex]\(-2\)[/tex]:
[tex]\[ -2(3x + \frac{1}{2}y = 3) \][/tex]
This gives us:
[tex]\[ -6x - y = -6 \quad \text{(3)} \][/tex]

Now, add the modified equation (3) to equation (2) to eliminate the [tex]\(x\)[/tex]-terms:

[tex]\[ (-6x - y) + (6x - y) = -6 + 2 \][/tex]

Simplifying, we get:
[tex]\[ -2y = -4 \][/tex]
[tex]\[ y = 2 \][/tex]

Thus, [tex]\(\boxed{\text{Multiply the first equation by -2}}\)[/tex] is the correct operation to eliminate the [tex]\(x\)[/tex]-terms.

### Part 2: Eliminating the [tex]\(y\)[/tex]-terms

To eliminate the [tex]\(y\)[/tex]-terms, we can make the coefficients of [tex]\(y\)[/tex] in both equations equal in magnitude but opposite in sign.

1. Original equations:
[tex]\[ 3x + \frac{1}{2}y = 3 \quad \text{(1)} \][/tex]
[tex]\[ 6x - y = 2 \quad \text{(2)} \][/tex]

2. Multiply the first equation (1) by 2:
[tex]\[ 2(3x + \frac{1}{2}y = 3) \][/tex]
This gives us:
[tex]\[ 6x + y = 6 \quad \text{(4)} \][/tex]

Now, add the modified equation (4) to equation (2) to eliminate the [tex]\(y\)[/tex]-terms:

[tex]\[ (6x + y) + (6x - y) = 6 + 2 \][/tex]

Simplifying, we get:
[tex]\[ 12x = 8 \][/tex]

Therefore, multiplying the first equation by 2 does not eliminate the [tex]\(y\)[/tex]-terms properly.

### Part 3: Solving for [tex]\(x\)[/tex]

1. We found [tex]\(y = 2\)[/tex] earlier using elimination by eliminating [tex]\(x\)[/tex]-terms.
2. Substitute [tex]\(y = 2\)[/tex] back into the original first equation to solve for [tex]\(x\)[/tex]:

[tex]\[ 3x + \frac{1}{2}(2) = 3 \][/tex]
[tex]\[ 3x + 1 = 3 \][/tex]
[tex]\[ 3x = 2 \][/tex]
[tex]\[ x = \frac{2}{3} \][/tex]

So, the solution to the system is:
[tex]\[ (x, y) = \left(\frac{2}{3}, 2\right) \][/tex]

The solution is [tex]\(\boxed{\left(\frac{2}{3}, 2\right)}\)[/tex].